The future of business schools: Purpose, action, and impact - BALDEGGER, Rico (Institutional Knowledge at Singapore Management University, 2022)
Are business schools on the wrong track? For many years, business schools enjoyed rising enrollments, positive media attention, and growing prestige in the business world. However, due to the disruption of Covid-19, many previously ignored issues relating to MBA programs resurfaced. As a result, MBA programs now face lower enrollments and intense criticism for being deficient in preparing future business leaders and ignoring essential topics like ethics, sustainability, and diversity and inclusion. The Future of Business Schools discusses these issues in the context of three critical areas: complexity, sustainability, and destiny.